Bordered Rights: Legal Political Barriers to Women’s Health and HIV Services Timor Leste–Indonesia Borderlands - da Silva, Dulce Martins (Al-Risalah, 2025)
The purpose of this study was to examine the legal and political barriers affecting women's access to HIV/AIDS services in the Timor-Leste–Indonesia region. The study focused on how social stigma, legal conditions, and national borders create structural vulnerabilities, particularly for undocumented women living in rural areas. Qualitative methods were used, with data collected through interviews and observations with health care providers, individuals living with HIV/AIDS, local NGO staff, and policymakers, using purposive and snowball sampling approaches to identify individuals with relevant expertise and knowledge to participate. Data were then compiled from journal articles and legislation relevant to the research theme. Thematic analysis was used to identify key points in informants' narratives. Key findings of the study include fragmented legal systems between the two countries, stigma and discrimination among institutionalized groups, political pressure on vulnerable populations, and geographic barriers that hinder access to services. Women living with HIV/AIDS on the Indonesia-Timor Leste border face pressing health protection challenges due to limited cross-border services, social stigma, and legal barriers. Without structural interventions, they continue to be marginalized and at high risk. The study urges bilateral health agreements, gender-sensitive training, and recognition of community-based efforts to improve healthcare access and protect vulnerable women in marginalized border areas.